An Information Framing Through Newspaper Media: Knowledge Transfer on Children - Febriyanto, Febriyanto; Sadikin, Mohammad Aufar (UI Scholars Hub, 2020)
The Kompas newspaper is known as a daily for adults, but there is a rubric aimed at children called the Kompas Anak rubric. it is important to see how the framing, starting from the knowledge, information, messages, illustrations or drawings, writing, words and sentences that differ between children and adults. This study examines the transfer of knowledge through the